Passive OCT probe head for 3D duct inspection - Ford, Helen D.; Tatam, Ralph P. (IOP Publishing, 2013)
A passive, endoscopic optical coherence tomography (OCT) probe has been demonstrated, incorporating an imaging fibre bundle and 45° conical mirror, and with no electromechanical components at the probe tip. Circular scanning, of the beam projected onto the proximal face of the imaging bundle, produces a corresponding circular scan at the distal end of the bundle. The beam is turned through 90° by the conical mirror and converted into a radially-scanned sample beam, permitting circumferential OCT scanning in quasi-cylindrical ducts. OCT images, displayed as polar plots and as 3D reconstructions, are presented, showing the internal profile of a metallic test sample containing a 660µm step in the internal wall. Results have been acquired using two methods: one that makes use of multiple beam-circle diameters, and a mechanical 'pull-back' technique. The effects of the convex surface of the conical mirror on spatial resolution are discussed, with suggested working distances given for different application regimes.